Thermal and oxidative degradation of morpholine and blendof piperazine and diethanolamine for CO2 capture / Shaukat Ali - Ali, Shaukat (2016)

(untitled)
Amine-based post-combustion carbon capture (PCC) technology is one of the mature options to contribute to the mitigation of CO2 emissions. The benchmark amine for this technology is monoethanolamine (MEA). MEA undergoes irreversible reactions, resulting loss of its concentration under process operating conditions. Degradation of solvent may cause environmental concerns, increased costs and process operation problems. Current effort is made to look into the thermal and oxidative degradation of (30.34 wt.%) morpholine (MOR) and (31.5 wt.%) blend of piperazine (PZ) and diethanolamine (DEA). Thermal degradation experiments were conducted using 316 stainless steel cylinders closed with Swagelok endcaps, which were kept in convection ovens. Degraded samples were analyzed by using Gas Chromatography (GC) with Flame Ionization Detector (FID) for final concentration of parent amines and GC with Mass Spectrometry (MS) was used for identification of degradation products. Thermal degradation of MOR was investigated with CO2 loadings of 0.0-0.48 mol CO2/mol alkalinity at 135-190 °C. Whereas, thermal degradation of PZ/DEA (0.8 m/3.2 m) was investigated at 135 °C with CO2 loading of 0.0 to 0.40 mol CO2/mol alkalinity. Oxidative degradation experiments of the both systems were conducted in a low gas flow, 1-liter stirred tank semi-batch jacketed glass reactor. In oxidative degradation, O2 partial pressure was varied from 50 to 90 kPa and three temperatures 40, 50 and 60 °C were used for both systems. Results of thermal degradation of MOR showed that MOR is stable up to 150 °C. However, it degrades significantly at 175 °C and higher temperatures. CO2 loading had also a direct effect on loss of MOR. A kinetic model is proposed for rate of degradation of MOR, statistically, which fits experimental data well. In comparison with other amines like MEA, DEA, methyldiethanolamine (MDEA) and PZ, the MOR is the most stable amine at elevated iv temperatures. Oxidation of MOR increases by increasing both temperature as well as O2 partial pressure. A kinetic model has been proposed for the oxidation of MOR. Predicted results of model are compared with those of obtained through experiments, which statistically show that the model is well representative of MOR oxidation. In thermal degradation of blended system, loss of PZ was higher than other investigated blends of PZ like PZ/MDEA, PZ/aminomethylpropanol (AMP), and PZ/MEA under similar experimental conditions. CO2 loading increased the rate of degradation of both PZ and DEA. Concentration of PZ approached to zero within 300 hours of experiment at high CO2 loading. Empirical rate equations are proposed for their thermal degradation of both PZ and DEA. Model of PZ is well representative of the experimental data, whereas model of DEA lacked the fitting of experimental data. Oxidative degradation experimental results of blend indicate that loss of PZ is very high in presence of DEA and it increases as O2 partial pressure and temperature are on rise. Degradation rate models for PZ and DEA are found to fit experimental data very well. Coefficients of the models indicate that loss of PZ and DEA are a function of Oxygen concentration and temperature.